PREDICTIVE MAINTENANCE ANALYSIS OF LIGHTNING RODS BASED ON INFRARED THERMOGRAPHY AT 150 KV GARUT SUBSTATION - sabilatul, anisa (Jurnal Informatika dan Teknik Elektro Terapan, 2026)
A vital component in a substation is a lightning arrester that plays a role in protecting components from overvoltage due to lightning strikes and switching maneuvers. This study aims to analyze the application of a predictive maintenance method based on infrared thermography to detect early arrester degradation in the 150 KV Garut Substation. The research method is carried out by measuring the temperature on the connection clamp and conductor using a thermovision camera, calculating ∆T (delta-T) according to PLN standards, determining the emissivity value, and validating the method with accuracy and precision calculations. The measurement results from 68 connection points show that all points are still in the good condition category with ∆T values ​​below the danger threshold. From 28 emissivity measurement samples, an average of 0.9990 was obtained with a coefficient of variation of 0.19% and an accuracy of 99.91%, indicating that the measurement method is suitable for use as an equipment condition monitoring system. These findings prove that infrared thermography is effective as an early detection tool for thermal anomalies and supports increasing the reliability of the electricity transmission system